Dose coefficients for ICRP reference pediatric phantoms exposed to idealised external gamma fields. (24th January 2017) - Chang, Lienard A; Simon, Steven L; Jorgensen, Timothy J; Schauer, David A; Lee, Choonsik
Abstract: Organ and effective dose coefficients have been calculated for the International Commission on Radiological Protection (ICRP) reference pediatric phantoms externally exposed to mono-energetic photon radiation (x- and gamma-rays) from 0.01 to 20 MeV. Calculations used Monte Carlo radiation transport techniques. Organ dose coefficients, i.e., organ absorbed dose per unit air kerma (Gy/Gy), were calculated for 28 organs and tissues including the active marrow (or red bone marrow) for 10 phantoms (newborn, 1 year, 5 year, 10 year, and 15 year old male and female). Radiation exposure was simulated for 33 photon mono-energies (0.01–20 MeV) in six irradiation geometries: antero-posterior (AP), postero-anterior, right lateral, left lateral, rotational, and isotropic. Organ dose coefficients for different ages closely agree in AP geometry as illustrated by a small coefficient of variation (COV) (the ratio of the standard deviation to the mean) of 4.4% for the lungs. The small COVs shown for the effective dose and AP irradiation geometry reflect that most of the radiosensitive organs are located in the front part of the human body. In contrast, we observed differences in organ dose coefficients across the ages of the phantoms for lateral irradiation geometries. We also observed variation in dose coefficients across different irradiation geometries, where the COV ranges from 18% (newborn male) to 38% (15 year old male) across idealised whole body irradiation geometries for the major organs (active marrow, colon, lung, stomach wall, and breast) at the energy of 0.1 MeV. Effective dose coefficients were also derived for applicable situations, e.g., radiation protection or risk projection. Our results are the first comprehensive set of organ and effective dose coefficients applicable to children and adolescents based on the newly adopted ICRP pediatric phantom series. Our tabulated organ and effective dose coefficients for these next-generation phantoms should provide more accurate estimates of organ doses in children than earlier dosimetric models allowed.